(3GSJQGJjLjGJ GdGSJKeGQ aj HhQUI GdGhQGb GdeGdjI (B:s (3CSge (B- (3SfOGJ (B- (3hKGFb GdGSJKeGQ (B- (3GdNjGQGJ (B/s - (3Mfaj, YHO GdZaGQs ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2007)
(3jYGdL GdcJGH GdaUhd GdJGdjI (B:(3GdESJKeGQ aj GdChQGb GdeGdjI ,bjGS YGFO h eNGWQ GdChQGb GdeGdjI ,GdeSJMOKGJ aj fXQjI GdESJKeGQ h caGAI CShGb QCS GdeGd ,GdeONd dJMdjd GdCSge ,JMdjd h Jbhje GdSfOGJ ,CShGb QCS GdeGd aj eUQ ,GdNjGQGJ(B. s
(3HjHdjhZQGajG U(B.501 s
Keywords: (3GSJKeGQs; (3GhQGb eGdjIs; (3HhQUIs